Residual Stresses Analysis in Ball end Milling of Nickel-Based Superalloy Inconel 718 - Wang,Junteng (2017)
Inconel 718 is widely used in the aviation, space, automotive and biomedical industries because of its outstanding properties. Near-surface residual stresses that are induced by ball end milling in Inconel 718 can be crucial for the performance and service time of the machined parts. In this paper, the influences of cutting conditions, including the use of cutting parameters, cutting fluid and spindle angles, on the residual stresses in the ball end milling process of Inconel 718 alloy were investigated experimentally. X-ray diffraction measurements reveal that residual stress distributions are highly influenced by cutting parameters, especially the depth of cut and cutting speed. The milling operation with cooling induces more compressive stresses trend and the magnitude of the residual stresses increases in the tensile direction with the increase of spindle angles. These cutting induced effects were further discussed with respect to thermal- mechanical coupling theory and some observations made by optical microscopy. From this investigation, it is suggested that the machining process parameters are not the smaller the better for the control of residual stresses in the ball end milling process of Inconel 718.